Age at Smoking Initiation and Prevalence of Cigarette Use Among Youths in Sub-Saharan Africa, 2014-2017 - Chido-Amajuoyi, Onyema Greg (JAMA Netw Open, 2021)
This cross-sectional study examines age at smoking initiation, prevalence of cigarette use, and prevalence of exposure to smoking-related risk factors among youths in sub-Saharan Africa.